PENGARUH TENAGA KERJA, BAHAN BAKU DAN PRODUKSI TERHADAP PENDAPATAN PENGERAJIN INDUSTRI KERAJINAN KAYU DI KABUPATEN GIANYAR - Budhi Laksana, I Nyoman Darma; Jember, I Made (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 7, No. 8, Agustus 2018 (pp. 1587-1825), 2018)
The province of Bali has great potential in the trade of wooden handicrafts. Viewed from the development of Bali's regional exports from 2013 to 2016, including wooden handicrafts, where own wooden handicrafts have contributed to the provision of more jobs. The purpose of this study is to analyze the direct influence of labor and raw materials on production in the wood craft industry in Gianyar regency, to analyze the direct influence of labor, raw materials and production on income in the wood craft industry in Gianyar regency, and to analyze the indirect effect labor and raw materials to income through production in the wood craft industry in Gianyar regency. Data analysis technique used is path analysis technique (Path Analysis) and Sobel analysis. The results showed that labor and raw materials have a direct and positive effect on the production of wood craftsmen in Gianyar regency. Labor, raw materials and production have a direct positive and significant effect on the income of wood craftsmen in Gianyar regency. Labor and raw materials indirectly affect income through production or in other words production is a variable that mediates the effect of labor and raw material on the income of woodworkers in Gianyar regency